2022
DOI: 10.1039/d1cy01823j
|View full text |Cite
|
Sign up to set email alerts
|

Facet-dependent activity of shape-controlled TiO2 supported Au nanoparticles for the water–gas shift reaction

Abstract: The bifunctional role of noble metal/oxide interface in the activation of reactants is of vital importance in heterogeneous catalysis of water-gas shift (WGS) reaction. Herein, three types of shape-controlled TiO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Flytzani-Stephanopoulos and a co-worker 15 found that the CeO 2 -morphology-dependent oxygen vacancy concentrations determined the number of strongly bound Au atoms and consequently the catalytic activity in the WGS reaction. Tang et al 16 observed TiO 2 -morphology-dependent catalytic activity of Au/TiO 2 catalysts in the WGS reaction, which was associated with TiO 2 shape-dependent reducibility and intermediate decomposition. As far as we know, oxide shape effects have not been explored on Pt/oxide catalysts for the WGS reaction, although they are widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Flytzani-Stephanopoulos and a co-worker 15 found that the CeO 2 -morphology-dependent oxygen vacancy concentrations determined the number of strongly bound Au atoms and consequently the catalytic activity in the WGS reaction. Tang et al 16 observed TiO 2 -morphology-dependent catalytic activity of Au/TiO 2 catalysts in the WGS reaction, which was associated with TiO 2 shape-dependent reducibility and intermediate decomposition. As far as we know, oxide shape effects have not been explored on Pt/oxide catalysts for the WGS reaction, although they are widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition and formation mechanisms of Au NPs depend on the morphology, crystal structure, and crystal phase composition of the semiconductor [36][37][38][39]. Due to the non-covalent interaction between TiO2 and Au NPs, the deposition of Au NPs is favored on the anatase crystal phase [40,41].…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Commercial TiO2′s anatase diffractions are located at 25.2° and 37.8°, whereas in the case of the Au/TiO2/WO3 heterostructures, these peaks are situated at 25.4° and 37.1°; thus, the slight shifts in the anatase peaks could be linked to the presence of Au NPs on anatase TiO2. The probability that Au NPs are deposited on anatase TiO2 is extremely high since the crystal phase composition of commercial TiO2 is The deposition and formation mechanisms of Au NPs depend on the morphology, crystal structure, and crystal phase composition of the semiconductor [36][37][38][39]. Due to the non-covalent interaction between TiO 2 and Au NPs, the deposition of Au NPs is favored on the anatase crystal phase [40,41].…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%